The association of systemic inflammatory markers with indicators of stress and cardiac necrosis in patients undergoing aortic valve replacement and revascularization surgeries - Saracevic, A; Medved, I; Hrabric Vlah, S; Kozmar, A; Bilic-Zulle, L; Simundic, A M (Physiological research, 2020)
The aim was to investigate: changes of inflammatory, stress and cardiac response in patients undergoing open heart surgeries up to five days after the procedure; the association between inflammatory, stress and cardiac response and whether changes in a certain marker can predict short-term patient outcome. Ninety patients were divided into three groups, 30 participants each (on-pump,off-pump revascularization and valve replacement group). The following markers were measured:complete blood count, CRP, IL-6, IL-10, leptin, resistin, monocyte chemoattractant protein-1 (MCP-1), cortisol, CK and hsTnT in 5 points. Resistin increased in all three groups. Lower IL-10 levels were found after the surgery and higher levels of leptin and MCP-1 in the off-pump than in the on-pump group. Off-pump group had higher values of IL-6, IL-10, leptin, resistin and MCP-1 and lower levels of CK and hsTnT 24 after surgery than the on-pump group. We found significant correlation between MCP-1 and resistin. The difference between resistin at time points 2 and 3 significantly predicted transfusion needs; while the difference between CRP and resistin before and at the end of the surgery together with the difference between leukocytes at the end and 24 hours after the surgery predicted the use of inotropic agents/vasopressors. Cardiac surgeries cause an increase of inflammatory, stress and cardiac markers. Only resistin correlated with MCP-1 which confirms the link between resistin secreted form infiltrated macrophages and enhanced release of MCP-1.
Keywords: dospělí; Aortic Valve Disease; revaskularizace myokardu; Female; biologické markery; onemocnění aortální chlopně; oxidační stres; Biomarkers; Adult; mladý dospělý; ženské pohlaví; Oxidative Stress; Myocardial Revascularization; lidé; Inflammation Mediators; nekróza; Aged, 80 and over; Necrosis; Middle Aged; nemoci koronárních tepen; Male; Aged; Young Adult; Coronary Artery Disease; koronární bypass; mediátory zánětu; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Coronary Artery Bypass; Humans